Expression signature of miRNAs and the potential role of miR‐195‐5p in high‐glucose–treated rat cardiomyocytes. Issue 2 (15th November 2019) - Shi, Yuanqi; Yan, Caichuan; Li, Yang; Zhang, Yuhao; Zhang, Guocui; Li, Mingzhu; Li, Baoxin; Zhao, Xin
Abstract: MicroRNAs are endogenous small noncoding RNAs that posttranscriptionally regulate the expression of target genes and play crucial roles in diverse physiopathologic processes. In the current study, we examined the microRNA (miRNA) expression profile of high‐glucose–treated neonatal rat cardiomyocytes and the potential mechanisms. Differentially expressed miRNAs were analyzed by a miRNA microarray and validated by a quantitative real‐time polymerase chain reaction in high‐glucose–treated rat cardiomyocytes. Based on the results of our previous study and the bioinformatics prediction, we identified miR‐195‐5p/SGK1/Nedd4‐2/hERG as the top‐ranked signal pathway in diabetes cell model in vitro. In summary, our present study provides novel insights into the regulatory mechanism of miR‐195‐5p/SGK1/Nedd4‐2/hERG in rat cardiomyocytes under high‐glucose stress, which may provide a novel idea for the development of diagnostic and therapeutic strategies for diabetic cardiomyopathy in the future.